Gratias agamus Deo: a reflection on specificity in our Eucharistic prayers - O'Loughlin, Thomas (Australian Academy of Liturgy, 2017)
It is now almost fifty years since the introduction of a variety of Eucharistic prayers in the Roman rite. Over that time we have become so familiar with the idea of a variety of Prayers that it is hard to imagine how controversial the ideaof any companions for the Roman Canon seemed when it was first mooted by Hans Küng around the time of the Council.1 However, we may also have become so familiar with the prayers that have become standard elements within our liturgy that we may not recognize that the journey towards a better liturgy is not confined to great moments of reform (such as that which occurred after the Second Vatican Council) but is a continuing process. It is the purpose of this paper to draw attention to just one aspect of this process, highlighting some aspects of the anaphora to which we need to give more consideration in future.